"We're Trying so Hard for Outcomes but at the Same Time We're not Doing Enough": Barriers to Physical Activity for Australian Young People in Residential Out-of-home Care. Issue 4 (2nd October 2022) - Green, Rachael; Bruce, Lauren; O'Donnell, Renee; Quarmby, Tom; Hatzikiriakidis, Kostas; Strickland, David; Skouteris, Helen
ABSTRACT: Despite the clear benefits of engaging in regular physical activity (PA), research suggests that young people in Out-of-Home Care (OoHC) are less likely to achieve the recommended levels of PA than their same-aged counterparts in the general community. To date, there has been limited examination of the barriers to PA engagement specific to young people living in residential OoHC. This qualitative study aimed to better understand the barriers and/or challenges to regular PA engagement for young people in residential OoHC. The voice of young people, residential care staff, and key stakeholders in the OoHC sector were included through the use of interviews and focus groups. Three key barriers were identified including: (1) the residential OoHC setting is not conducive to PA; (2) young people require additional support to be physically active; and (3) there are community barriers which impact young people's engagement in PA. Discussions identified a number of individual barriers or challenges faced by young people, which are impacted or exacerbated by the barriers faced at the system and community level. Findings suggest there is a need for governments, agencies involved in OoHC and community sports and recreation facilities to re-examine current practices and policies and address barriers related to workloads of residential care staff, funding, resource allocations, and capacity to support young people's participation in PA. The need to take action is urgent and warranted. It is recommended that future intervention approaches develop innovative partnerships—that bring together research, practice, community, and policy resources—to ensure access to PA does not become an equity issue for YP living in residential OoHC.